2019
DOI: 10.1002/cplu.201800597
|View full text |Cite
|
Sign up to set email alerts
|

2,5‐Dimethoxybenzene‐1,4‐dicarboxaldehyde: An Emissive Organic Crystal and Highly Efficient Fluorescent Waveguide

Abstract: To identify the simplest organic structure for an emitter, we focused on 2,5‐dimethoxybenzene‐1,4‐dicarboaldehyde. This symmetric molecule has a very low molecular weight (MW=194), a single benzene unit, and consists of only three elements (H, C and O). It forms highly efficient and pure emitting crystals (λem=499 nm, ΦF=0.42, FWHM=42 nm) due to the rigid structure based on the single benzene framework and four intramolecular hydrogen bonds between electron‐donating methoxy and electron‐accepting aldehyde grou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 33 publications
(15 citation statements)
references
References 32 publications
0
15
0
Order By: Relevance
“…DMTA is an efficient fluorophore in organic solvents and solid state and its fluorescence is attributed to the formation of hydrogen bonds that rigidify the structure. 55 Thus, exfoliation of the material is able to restore this emission, mainly in acidic medium, which seems to be related with the protonation of the nitrogen atoms in the imine groups ( vide infra ). It was observed that the intensity and position of both emission bands depend on the THF/water ratio.…”
Section: Resultsmentioning
confidence: 99%
“…DMTA is an efficient fluorophore in organic solvents and solid state and its fluorescence is attributed to the formation of hydrogen bonds that rigidify the structure. 55 Thus, exfoliation of the material is able to restore this emission, mainly in acidic medium, which seems to be related with the protonation of the nitrogen atoms in the imine groups ( vide infra ). It was observed that the intensity and position of both emission bands depend on the THF/water ratio.…”
Section: Resultsmentioning
confidence: 99%
“…1a) was obtained from 4-bromobenzyl cyanide and 2,5-dimethoxybenzene-1,4-dicarboxaldehyde. 25 Reddish orange-colored needle-like crystals were grown from 1,2-dichloroethane (Fig. 1b).…”
Section: Resultsmentioning
confidence: 99%
“…19 Single benzene emitters have been widely investigated and they can readily form high-quality crystals. [48][49][50][51][52] By employing a single benzene emitter 1, here we report two organic polymorphs that display quite different emission and mechanical properties. Two crystals 1B and 1G were obtained by screening various crystallization conditions.…”
Section: Introductionmentioning
confidence: 90%